2014
DOI: 10.11648/j.edu.20140304.11
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Analysis of Students’ Learning and Achievements: A Motivational Approach

Abstract: Abstract:The present study details a theoretical-conceptual model, scoping the interrelations between antecedents (academic buoyancy, emotional and physiological states, task value), cognitive processes (habitual action, critical reflection), and adaptive outcomes (academic engagement, academic achievement) in the context of educational psychology. 294 (151 men, 143 women) first-year university students participated in this study. Likert-scale inventories were administered to students and used to elicit releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 73 publications
(133 reference statements)
0
17
0
Order By: Relevance
“…12; engagement have been demonstrated by correlational and longitudinal studies (e.g., Phan & Ngu, 2014b;Phan, 2014c) to be robust predictors of students' achievement outcomes. From a correlational perspective, for example, Phan and Ngu (2014b) conducted a study among 294 university students, and found that vigor, dedication, and absorption (combined as a unitary construct) significantly predicted students' performance ( .54, .001). Casuso-Holgado et al's (2013) study similarly showed, among 304 university students, that vigor, dedication, and absorption were strongly associated with students' GPA.…”
Section: The Association Between Vigor Dedication and Absorption DImentioning
confidence: 98%
See 1 more Smart Citation
“…12; engagement have been demonstrated by correlational and longitudinal studies (e.g., Phan & Ngu, 2014b;Phan, 2014c) to be robust predictors of students' achievement outcomes. From a correlational perspective, for example, Phan and Ngu (2014b) conducted a study among 294 university students, and found that vigor, dedication, and absorption (combined as a unitary construct) significantly predicted students' performance ( .54, .001). Casuso-Holgado et al's (2013) study similarly showed, among 304 university students, that vigor, dedication, and absorption were strongly associated with students' GPA.…”
Section: The Association Between Vigor Dedication and Absorption DImentioning
confidence: 98%
“…A plethora of empirical studies have suggested a number of motivational and social antecedents that could encourage and cultivate students' proactive engagement. Motivational antecedents include, for example, self-efficacy (e.g., Breso et al, 2011;Phan, 2014c;Phan & Ngu, 2014a;Ouweneel et al, 2013;Reeve & Lee, 2014;Phan, 2014b;Wang & Eccles, 2013), task value (e.g., Wang & Eccles, 2013;Martin, Way, & Anderson, 2015;Phan & Ngu, 2014b;Fan, 2011), and mastery goal orientation (e.g., Wang & Holcombe, 2010;Reeve & Lee, 2014;Phan, 2014a;Gonida, Voulala, & Kiosseoglou, 2009). In addition, empirical findings have produced salient social antecedents of engagement that include, for example, parents' and teachers' support (e.g., Perry, Liu, & Pabian, 2010;Wang & Holcombe, 2010;Wang & Eccles, 2013;Brewster & Bowen, 2004;Wang & Eccles, 2012b;Estell & Perdue, 2013).…”
Section: In Totalitymentioning
confidence: 99%
“…One of these cognates is resilience which seems equal to buoyancy, but in reality, it differs from it. While both concepts have a similar theoretical ground, resilience has limited applicability in academia as it does not clarify the adversities that routinely happen in one's academic life (Phan and Ngu, 2014). Moreover, resilience has definitional, sampling and population, operational, and methodological distinctions with academic buoyancy (Jahedizadeh et al, 2019).…”
Section: The Cognates Of Academic Buoyancymentioning
confidence: 99%
“…Pintrich (2000aPintrich ( , 2000b outlined a model of the relations between motivation and cognition. Students placing value on their academic work tend to put in more effort, thus spending more time in task engagement (Phan & Ngu, 2014). Recent studies have shown how one's prior academic successes and failures can influence future levels of engagement and motivation (e.g., Sinatra, Heddy, & Lombardi, 2015;Sitzmann & Ely, 2011).…”
Section: Self-regulated Learning and Motivationmentioning
confidence: 99%